2010
DOI: 10.3844/pisp.2010.57.64
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Calculation of the Optical Absorption of Silver and Gold Nanoparticles by Density Functional Theory

Abstract: Problem statement: Metal nanoparticles confine the motion of conduction electrons and exhibit a strong optical absorption of electromagnetic radiation in the UV-vis-NIR region. The absorption is classically derived from the collective oscillations of free electrons in a metallic nanostructure as a consequence of incident electromagnetic radiation polarizing the particle optically embedded in a dielectric matrix. These oscillations, known as the localized surface Plasmon resonance has been modelled by Gustav Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…For a technical understanding, however, perhaps it should be left to the experts to scrutinize the complex physics and mathematics for obtaining and interpreting the theoretical data. In quantum physics, the absorption spectrum of metal nanoparticles may be described as a result of the intra-band excitations of conduction electrons from the lowest energy state to higher energy states within the conduction band of metal nanoparticles [56,57]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a technical understanding, however, perhaps it should be left to the experts to scrutinize the complex physics and mathematics for obtaining and interpreting the theoretical data. In quantum physics, the absorption spectrum of metal nanoparticles may be described as a result of the intra-band excitations of conduction electrons from the lowest energy state to higher energy states within the conduction band of metal nanoparticles [56,57]. …”
Section: Resultsmentioning
confidence: 99%
“…The final term is the non-classical exchange-correlation energy containing all the remaining quantum effects not captured by the kinetic energy; the classical Coulomb potential with C e is the Thomas–Fermi–Dirac non-classical exchange-correlation energy constant [63]. Details of the quantum mechanical treatment can be found in our earlier publications [56,57]. It can be shown that the relation between the density and absorption may be written as ρ ≈ ( Z /σ) 3/2 , where Z is the atomic number.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, optical absorption of metal nanoparticles based on quantum mechanics has been proposed [43,44] and confirmed experimentally [38,45]. In this theory of metal nanoparticles, the absorption of light can be described as a result of non-radiative intra-band excitations of conduction electrons from the lowest energy state assigned by the quantum numbers to higher energy states near the Fermi level of the conduction band.…”
Section: Conduction Band Of Ni Nanoparticlesmentioning
confidence: 99%
“…Moreover, decreasing bacterial population in vase solution by SNPs might be decrease bacterial contamination in vessels. When metallic particles grown and became big, its peak at spectrophotometers graph will shift to long wave in red area (Gharibshahi and Saion, 2010). However, it can be concluded that plant extracts or bacteria extracts did not affect on nano-particles stability and aggregations (Ashrafi et al, 2010).…”
Section: Nano-particles Stabilitymentioning
confidence: 99%